2021
DOI: 10.4102/sajhrm.v19i0.1437
|View full text |Cite|
|
Sign up to set email alerts
|

The moderating role of career adaptability on the relationship between workplace spirituality and employee mental and physical health

Abstract: Orientation: Aspects of religion and spirituality are now being infused into the experience of work. The key to this is understanding how religion and spirituality affect individual and organisational functioning.Research purpose: This study investigated the influence of career adaptability on workplace spirituality and employee health. In this study, employee health refers to mental and physical health.Motivation for the study: This study’s context was the South African public service noted to be undergoing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 81 publications
(99 reference statements)
0
10
0
1
Order By: Relevance
“…In promoting decent working conditions, organisations may also potentially help in promoting aspects of physical health (Duffy et al 2021 ). Findings in this study contribute to the literature on health development within the South African public service; notably, focus has been chiefly centred on employee mental health (Mathibe & Chinyamurindi 2021 ; Shava & Chinyamurindi 2021 ). Physical health promotion is argued for in this study.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…In promoting decent working conditions, organisations may also potentially help in promoting aspects of physical health (Duffy et al 2021 ). Findings in this study contribute to the literature on health development within the South African public service; notably, focus has been chiefly centred on employee mental health (Mathibe & Chinyamurindi 2021 ; Shava & Chinyamurindi 2021 ). Physical health promotion is argued for in this study.…”
Section: Discussionmentioning
confidence: 71%
“…The working conditions in an organisation can significantly impact the health of employees (Shava & Chinyamurindi 2021 ). The organisational climate comprises how work is organised and the responses that accompany all this from a leadership perspective (Chinyamurindi, Mathibe & Marange 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has found that career adaptability affected mental health at work, and vice versa. Shava and Chinyamurindi (2021) conducted a study in the education sector to understand the relationship between career adaptability and health reported that teachers with good career adaptability showed improvements in both mental and physical health. A study on personality traits and emotional intelligence on career adaptability among teachers of special education showed a positive connection between emotional intelligence, conscientiousness, extraversion, openness to experience, and career adaptability, with the last two as the strongest predictors of career adaptability (Er & Rameli, 2019).…”
Section: Introductionmentioning
confidence: 99%